Społeczność szkoły polonijnej w Leuven (Belgia) jako wspólnota komunikatywna = The Polish school environment in Leuven (Belgium) as an example of a specific speech community - Lewińska, Aneta; Radomska-T`Seyen, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to present the school community gathered around a Polish facultative school as a speech community in a broad sense. In our considerations, we use a variety of definitional approaches to define this group, characterise the conditions of being part of the Polish speech community, and identify smaller subgroups with common characteristics. We introduce the notion of educational discourse in the perspective of the activities of a facultative school in order to characterise the connecting relations and communication style between the participants of the school environment.
Keywords: wspólnota komunikatywna; Polonia belgijska; szkoła polonijna; dyskurs edukacyjny; językoznawstwo kulturowe; communicative community; Polish school in Belgium; educational discourse; cultural linguistics